Veterinary perspectives on the urbanization of leishmaniosis in Morocco - Lima, Clara; Bourquia, Maria; Zahri, Abderrahmane; Haissen, Nada; Santarém, Nuno; Cardoso, Luís; Cordeiro-da-Silva, Anabela (Parasites & Vectors, 2024)
Abstract Background Leishmaniosis caused by Leishmania infantum, L. major and L. tropica is endemic in Morocco. Growing evidence of both human and canine Leishmania infections in urban centres has been reported. Since many forms of the disease are zoonotic, veterinarians play an important role in leishmaniosis control by intervening at the parasite host level. This study aimed to bring together One Health principles to connect canine and feline leishmaniosis epidemiology within urban centres of Morocco (Rabat and Fez) and assess the level of awareness of Moroccan veterinarians about facing this threat.